2021
DOI: 10.25133/jpssv292021.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Growth Among Preterm MigrantChildren in Kanchanaburi Province, Thailand

Abstract: This research soughtto study the predictive factors of the duration of exclusive breastfeeding, mother’sfeeding behaviors,and health service accessibility onthe growth of preterm migrant children in Kanchanaburi Province, Thailand. The subjects were 156 Burmese migrant mothers with preterm children 18-24 months old who received health check-upsat well-baby clinics in Kanchanaburi Province. The data analysis was performed utilizingdescriptive and multiple logistic regression statistics. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a result of Thailand's low-cost healthcare insurance for migrant workers and their families to have access to healthcare services. 13 Therefore, no variation in access to healthcare scores, resulting in non-significant relationship between healthcare access and nutritional status.…”
Section: Original Article Smjmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of Thailand's low-cost healthcare insurance for migrant workers and their families to have access to healthcare services. 13 Therefore, no variation in access to healthcare scores, resulting in non-significant relationship between healthcare access and nutritional status.…”
Section: Original Article Smjmentioning
confidence: 99%
“…The explanation may be that preterm infants are more susceptible to infections, resulting in a poorer child growth rate, and unemployed migrant mothers employed exclusive breastfeeding for their child. 13…”
Section: Original Article Smjmentioning
confidence: 99%
“…Our study found a lower rate of healthcare utilization in urban area than rural area. In contrast, (Netithanakul and Soonthorndhada 2009)found people who live in urban areas use health care services more frequently than those in rural areas. A possible explanation is that elderly in urban area is able to access to some other health cares for their treatment such as drugstores and private clinic.…”
Section: Thailandmentioning
confidence: 92%